Psychosocial and environmental influences in early childhood and their relation to respiratory tract infections - Schuez-Havupalo, Linnea (fi=Turun yliopisto|en=University of Turku|, 2018)
Respiratory tract infections (RTIs) are most common in under-school-aged children, and they have a range of effects on society. In this study we aimed to examine modifiable risk factors relating to the young child’s immediate environments, namely the home, daycare, and free-time activities. This is a prospective birth cohort study carried out in Southwest Finland. We followed 1570 children for RTIs from birth until the age of 3 years, and documented medical-, psychological-, environmental-, and social factors applying diaries and questionnaires. A subset of 982 children were included in a more intensive infection follow-up, which included nasal swabs for virus analysis and visits at the study clinic during acute RTIs. We found maternal depressive symptoms during pregnancy to predict higher cumulative rates of acute otitis media by the age of 10 months in the infant, and maternal emotional loneliness to predict higher cumulative rates of physician visits within the same age frame. Acute otitis media, physician visits, and antibiotic consumption were marginally less frequent for infants of families with social loneliness in either or both parents. Comparing monthly sick days (days with symptoms of a RTI), antibiotic medications, and parental absences from work for children 0-24 months of age, we detected a steep rise of these measures after the start of daycare, and a subsequent clear decline within our follow-up, which ended 9 months after the initiation of daycare. When comparing the same outcome measures at the ages of 30-35 months of age, there were no significant differences for sick days between children in home care and those in out-of-home daycare. However, antibiotic medications were significantly more common for children in daycare centres, as compared to those in home care. When examining possible links between infant swimming activities and respiratory symptoms for children up to 17 months of age, no significant differences with respect to rates of RTIs could be observed. There was a statistically significant association between swimming and rhinovirusassociated wheeze for children with atopic eczema. This study strengthens our understanding on modifiable risk factors for RTIs in young children and is of relevance with respect to preventative strategies.

Psykososiaalisten ja ympäristötekijöiden vaikutukset hengitystieinfektioiden sairastamiseen varhaislapsuudessa. Hengitystieinfektioita esiintyy eniten alle kouluikäisillä lapsilla ja ne vaikuttavat monella tavoin ympäröivään yhteiskuntaan. Tämän tutkimuksen tavoitteena oli tutkia hengitystieinfektioiden modifioitavia riskitekijöitä, jotka liittyvät pienen lapsen arkisiin ympäristöihin: kotiin, päivähoitoon ja vapaa-ajan harrastuksiin. Tämä prospektiivinen syntymäkohorttitutkimus toteutettiin Varsinais-Suomen sairaanhoitopiirissä. Seurasimme 1570 lasta syntymästä 3 vuoden ikään hengitystieinfektioiden suhteen ja keräsimme tietoa terveyteen liittyvistä, psykologisista, sosiaalisista ja muista ympäristötekijöistä päiväkirjojen ja kyselykaavakkeiden avulla. Osa kohortista (982 lasta) osallistui tarkempaan infektioseurantaan, johon sisältyivät nenästä otetut näytteet virusmäärityksiä varten ja käynnit tutkimusvastaanotolla äkillisten hengitystieinfektioiden aikana. Äidin raskaudenaikaiset masennusoireet ennustivat välikorvatulehdusten suurempaa kumulatiivista määrää 10 kuukauden ikään mennessä ja äidin emotionaalinen yksinäisyys ennusti lääkärikäyntien suurempaa määrää samassa iässä. Välikorvatulehdukset, lääkärikäynnit ja antibioottikuurien määrä olivat hieman vähäisempiä sellaisilla lapsilla, joiden perheissä esiintyi sosiaalista yksinäisyyttä toisella tai molemmilla vanhemmilla. Alle 2-vuotiaiden lasten kuukausittaisten sairaspäivien määrä (päivät, jolloin lapsella oli hengitystieinfektion oireita), antibioottihoidot ja vanhempien poissaolot työstä lapsen sairauden vuoksi lisääntyivät voimakkaasti päivähoidon aloituksen jälkeen ja vähenivät sitten selvästi 9 kuukauden seurannan aikana. Kun vertasimme samoja vasteita 30-35 kuukauden iässä, hengitystieinfektiopäivien määrässä ei ollut merkitsevää eroa kotihoidossa ja kodin ulkopuolisessa päivähoidossa olevien lasten välillä. Antibioottikuureja oli kuitenkin merkitsevästi enemmän päiväkotihoidossa käyvillä lapsilla. Tutkimme myös mahdollisia yhteyksiä vauvauinnin ja hengitystieinfektioiden välillä 17 kuukauden ikään saakka. Hengitystieinfektioiden määrässä ei ollut eroa vauvauintia harrastaneiden ja muiden lasten välillä. Lapsilla, joilla oli atooppinen ihottuma, havaitsimme yhteyden vauvauinnin ja rinoviruksen aiheuttaman hengityksen vinkumisen välillä. Tutkimuksen tulokset lisäävät ymmärrystämme pienten lasten hengitystieinfektioiden modifioitavista riskitekijöistä ja antavat työkaluja ehkäisevien toimien kehittämiseen.